A method for annealing and pickling stainless steel strip surface after overheating
By using citric acid and acetic acid composite pickling solution and nano iron oxide wrapped in tartaric acid and vitamin C, combined with the use of corrosion inhibitors, the problems of oxide scale residue and environmental pollution during the annealing and pickling process of stainless steel in the prior art are solved, and the effect of efficient removal of oxide layers and reducing corrosion risks is achieved.
Patent Information
- Application Number
- CN202411236062.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-09-04
AI Technical Summary
In the existing stainless steel annealing and pickling methods, the commonly used nitric acid-based pickling solution will produce a large amount of nitrogen oxides, causing environmental pollution. At the same time, a single organic acid cleaning is difficult to completely remove the oxide scale, affecting the corrosion resistance and subsequent processing quality of stainless steel.
Using a pickling solution of citric acid and acetic acid, combined with tartaric acid and vitamin C-encapsulated nano iron oxide, effectively removes the oxide layer on the surface of stainless steel through physical friction and chelation, and adds corrosion inhibitors such as sodium benzoate and sunflower extract during the pickling process to reduce the corrosion risk of stainless steel.
It realizes effective removal of the oxide layer during the annealing and pickling process to avoid corrosion of stainless steel, and provides an environmentally friendly cleaning solution to reduce environmental pollution.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of annealing and pickling methods for stainless steel, and in particular to an annealing and pickling method for a stainless steel strip surface after overburning. Background Art
[0002] Stainless steel is widely used in the field of industrial machinery and daily life because of its bright and clean surface and good corrosion resistance. During the production and molding process of stainless steel, a layer of oxide scale will be generated on the surface due to high temperature and oxygen-containing environment. The commonly used nitric acid-based pickling solution will produce a large amount of nitrogen oxides during the pickling process, causing serious pollution to the surrounding environment. However, the use of a single organic acid for cleaning will easily leave oxide scale residue on the surface of the strip. If the stainless steel is not pickled properly, it will affect the subsequent cold rolling, such as the generation of pitting similar to small white lines; the residue of oxide scale will also have a certain impact on the corrosion resistance of stainless steel. Therefore, pickling has an important impact on the quality of stainless steel. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for annealing and pickling of the surface of a stainless steel strip after overburning. The method does not add pickling components with poor safety and environmental protection such as nitric acid and hydrofluoric acid. The method first uses a composite pickling solution of citric acid and acetic acid for pickling, and then adds a corrosion inhibitor. The method can effectively remove the oxide layer during the annealing and pickling process while avoiding stainless steel corrosion, which is environmentally friendly.
[0004] To achieve the above object, the technical solution adopted by the present invention is:
[0005] In a first aspect, the present invention provides a method for annealing and pickling a stainless steel strip surface after overburning, comprising the following steps:
[0006] S1. Annealing: Annealing the stainless steel strip after uncoiling;
[0007] S2, pickling: pickling the annealed stainless steel strip with a pickling solution for 5-10 minutes, adding a corrosion inhibitor for cleaning after pickling for 2-3 minutes; wherein the pickling solution comprises the following components by mass percentage: 10-15% citric acid, 5-10% acetic acid, 2-5% tartaric acid and nano iron oxide wrapped with vitamin C, which are supplemented to 100% by water; the corrosion inhibitor comprises the following components by mass percentage: 2-5% sodium benzoate, 1-2% nightshade extract, which are supplemented to 100% by water.
[0008] The present invention adopts a composite organic acid of citric acid and acetic acid as a pickling solution to remove the oxide layer on the metal surface. The nano iron oxide wrapped by tartaric acid and vitamin C can increase the contact area between the pickling and the metal surface, and provides a physical friction effect during the cleaning process to help remove the oxide layer. The wrapping of tartaric acid and vitamin C also improves the wettability of the iron oxide particles in the solution, making it easier for the cleaning solution to contact and penetrate into the oxide layer on the stainless steel surface. The nano iron oxide wrapped by tartaric acid and vitamin C has good dispersibility in the pickling solution, thereby increasing the contact area with the oxide layer on the stainless steel surface, improving the cleaning effect and cleaning efficiency. Tartaric acid and vitamin C are both polyhydroxy organic acids with a strong ability to chelate metal ions, and this chelation helps to stabilize the iron oxide particles and prevents them from aggregating or precipitating in an acidic solution. Among them, vitamin C is also a reducing agent, which helps to convert the oxide on the stainless steel surface, making it easier to be dissolved by citric acid and acetic acid. Moreover, the coating of tartaric acid and vitamin C optimizes this friction effect, and the coating layer may provide a certain degree of protection for the iron oxide particles, preventing them from over-reacting in the acidic environment, thereby reducing the potential corrosion risk to the stainless steel substrate.
[0009] Most importantly, the tartaric acid, vitamin C, citric acid and acetic acid in the pickling solution are all biodegradable organic acids. This combination provides an environmentally friendly cleaning solution with reduced impact on the environment.
[0010] Because organic acid is mainly used as the pickling liquid in the present invention, the pickling time will be slightly longer to ensure the pickling effect, but in order to avoid corrosion of stainless steel, a corrosion inhibitor is added during the pickling process.
[0011] Sodium benzoate in the corrosion inhibitor is the main corrosion-inhibiting component, and nightshade extract is a surfactant, which can effectively reduce the corrosion performance of stainless steel. The addition of sodium benzoate can reduce the risk of pitting and stress corrosion cracking, because it can form a uniform protective layer on the surface of stainless steel, preventing acid from directly contacting the metal, thereby reducing the corrosion rate during pickling. Moreover, sodium benzoate will decompose in an acidic solution to produce benzoic acid, which is a weaker acid, which can form a complex with the metal ions on the surface of stainless steel to further provide protection. Nightshade extract contains saponins, and the working principle of saponins is that its polar sugar head is hydrophilic, and the non-polar steroid or triterpene core is hydrophobic. This amphiphilic property makes the saponin molecules arranged on the surface of water to form a covering film, thereby reducing the mutual attraction between water molecules, resulting in a reduction in surface tension, so it can increase the contact area between the pickling solution and the stainless steel surface as a surfactant. The present invention selects nightshade extract and sodium benzoate for compounding, which has a synergistic effect, so that more metal surfaces are hindered by adsorption, resulting in a significant reduction in the corrosion rate of the stainless steel surface. Compared with some traditional corrosion inhibitors, such as nitrogen-containing organic corrosion inhibitors and sulfur-containing corrosion inhibitors, the corrosion inhibitors used in the present invention, sodium benzoate and nightshade extract from natural sources are more environmentally friendly and reduce the impact on the environment.
[0012] The method for preparing nano iron oxide coated with tartaric acid and vitamin C comprises the following steps:
[0013] The nano-iron oxide is dispersed in a mixed solution of tartaric acid and vitamin C, and a hydrothermal reaction is carried out at 150-200° C. for 10-15 hours. After cooling, the metal components are collected by a magnet, and after washing and drying, the nano-iron oxide coated with tartaric acid and vitamin C is obtained.
[0014] The present invention attaches tartaric acid and vitamin C to the surface of nano iron oxide through a hydrothermal reaction, so that the iron oxide particles have good dispersibility in the pickling liquid medium and reduce agglomeration.
[0015] Preferably, in step S1, the annealing treatment includes preheating, heating, soaking, slow cooling and rapid cooling steps in sequence; wherein the preheating temperature is 500-600°C and the time is 20-30min; the heating temperature is 700-1000°C and the time is 1-2h; the soaking temperature is 700-1000°C and the time is 2-3h; the rapid cooling parameters are: reducing the temperature to 30-50°C and the time is 10-30min.
[0016] The function of the preheating section: preheat the stainless steel material, reduce thermal stress, and avoid material damage caused by rapid heating.
[0017] The function of the heating section: heating to a temperature higher than the recrystallization temperature of stainless steel, promoting the recrystallization of grains, eliminating work hardening, and restoring the plasticity of the material.
[0018] The function of the soaking section is to ensure that the material reaches thermal equilibrium in all parts of the furnace and prepare for subsequent cooling.
[0019] The function of the slow cooling section: control the cooling rate, reduce thermal stress and internal stress, and avoid material cracking or deformation.
[0020] The function of the rapid cooling section is to quickly pass through the recrystallization and phase change temperature range, prevent carbide precipitation and phase change, and maintain the microstructure and properties of the material.
[0021] More preferably, if the stainless steel is austenitic stainless steel, the heating and soaking temperatures are both 900-1000°C; if the stainless steel is ferritic stainless steel, the heating and soaking temperatures are both 700-900°C. This is because austenitic stainless steel has a face-centered cubic (FCC) crystal structure, while ferritic stainless steel has a body-centered cubic (BCC) crystal structure. The FCC structure usually requires a higher temperature to promote atomic movement and recrystallization processes. Moreover, austenitic stainless steel usually contains higher chromium and nickel contents, and these elements have higher solid solubility in the FCC structure. High temperature annealing helps to uniformly distribute alloying elements such as chromium and nickel in the austenite matrix.
[0022] Preferably, in step S2, the pickling parameters are: temperature of 70-75° C., steel strip speed of 15-20 m / min, and pickling time of 5-10 min.
[0023] Preferably, the mass concentration of tartaric acid in the mixed solution of tartaric acid and vitamin C is 60-70%, and the concentration of vitamin C is 1-5%; the mass ratio of the mixed solution of tartaric acid and vitamin C to nano iron oxide is (5-6):1.
[0024] Preferably, the method for preparing nano iron oxide comprises the following steps:
[0025] Ammonium hydroxide, ferric chloride, ferrous chloride and water are mixed to obtain a mixed solution, and then a coprecipitation reaction is carried out. The reactant is washed and then dried to obtain the nano iron oxide; wherein the mass concentration of ammonium hydroxide in the mixed solution is 20-30%, the mass concentration of ferric chloride is 4-5%, and the mass concentration of ferrous chloride is 4-5%.
[0026] Preferably, the coprecipitation reaction parameters are: temperature of 20-40° C., stirring speed of 600-800 rpm / min, and time of 5-7 min.
[0027] Preferably, the source of the ferric chloride and ferrous chloride is stainless steel pickling waste liquid. In order to reduce resource waste, the source of the ferric chloride and ferrous chloride is stainless steel pickling waste liquid, which specifically includes the following steps:
[0028] pH adjustment: Adjust the pH of the wastewater to near neutral or slightly alkaline to promote the precipitation of iron ions. This can be achieved by adding alkaline substances such as sodium hydroxide (NaOH) or sodium carbonate (Na2CO3).
[0029] Precipitation: At the appropriate pH, iron ions react with hydroxide ions to form a precipitate, such as Fe(OH)3 or FeCO3. Through the precipitation process, iron can be separated from the solution;
[0030] Solid-liquid separation: Separate the precipitate from the waste liquid by filtration or centrifugation;
[0031] Washing: The collected precipitate is washed with deionized water to remove residual acid and other soluble impurities;
[0032] Drying: Dry the washed precipitate by methods such as drying or spray drying.
[0033] Calcination: The dried precipitate is calcined to decompose organic matter and oxidize iron hydroxide to produce iron oxide.
[0034] Chlorination: react iron oxide with a chlorinating agent (such as hydrogen chloride HCl or sodium chloride NaCl) to produce ferric chloride and ferrous chloride.
[0035] Dissolution and separation: Dissolve ferric chloride and ferrous chloride in a suitable solvent and then separate them by methods such as crystallization or evaporation.
[0036] Purification: The obtained ferric chloride and ferrous chloride are further purified, such as by recrystallization or ion exchange.
[0037] Preferably, the mass ratio of the pickling solution to the corrosion inhibitor is (3-4):1.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The present invention uses a composite organic acid of citric acid and acetic acid as a pickling solution to remove the oxide layer on the metal surface. The nano-iron oxide coated with tartaric acid and vitamin C can increase the contact area between the pickling and the metal surface, and the iron oxide particles provide physical friction during the cleaning process to help remove the oxide layer. The nano-iron oxide coated with tartaric acid and vitamin C has good dispersibility in the pickling solution, thereby increasing the contact area with the oxide layer on the surface of the stainless steel, improving the cleaning effect and cleaning efficiency. The tartaric acid, vitamin C, citric acid and acetic acid in the pickling solution are all biodegradable organic acids. This combination provides an environmentally friendly cleaning solution and reduces the impact on the environment. Because the pickling solution in the present invention is mainly organic acid, the pickling time will be slightly longer to ensure the pickling effect, but in order to avoid stainless steel corrosion, a corrosion inhibitor is added during the pickling process. Therefore, the annealing pickling method of the present invention can effectively remove the oxide layer during the annealing pickling process while avoiding stainless steel corrosion.
[0040] (2) Sodium benzoate in the corrosion inhibitor is used as the main corrosion inhibitor component, and nightshade extract is used as a surfactant, which can effectively reduce the corrosion performance of stainless steel. The nightshade extract and sodium benzoate are selected for compounding, which has a synergistic effect, so that more metal surfaces are adsorbed and blocked, resulting in a significant reduction in the corrosion rate at all concentrations. Compared with some traditional corrosion inhibitors, such as nitrogen-containing organic corrosion inhibitors and sulfur-containing corrosion inhibitors, the corrosion inhibitor used in the present invention is more environmentally friendly, and reduces the impact on the environment. DETAILED DESCRIPTION
[0041] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0042] The sources of reagents and equipment used in the following examples and comparative examples are as follows:
[0043] Citric acid solution: The manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd., the brand is C792200; the purity is 55% (w / w), the solution is water;
[0044] Acetic acid: The manufacturer is Shanghai Aladdin Biochemical Technology Co., Ltd., the brand is A11616, the purity is ≥99.8%;
[0045] Tartaric acid: The manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd., brand number D875395; purity ≥95%;
[0046] Vitamin C: manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd., brand number is A787795; purity is 2% (w / w), solution is water;
[0047] Nano iron oxide: The manufacturer is Hangzhou Hengna New Materials Co., Ltd., the brand is HN-E012, the particle size is 20~50nm;
[0048] Sodium benzoate: The manufacturer is Shanghai Haohong Biopharmaceutical Technology Co., Ltd., brand number 1034860, purity 98%;
[0049] Solanum nigrum extract: The manufacturer is Shaanxi Xinyanghe Biotechnology Co., Ltd.;
[0050] Ammonium hydroxide: ammonia solution, manufacturer is Shanghai Aladdin Biochemical Technology Co., Ltd., brand A291784; purity: 10.0 Normal
[0051] Ferric chloride: ferric chloride solution, the manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd., the brand is F766109, the purity is 38%, the solution is water;
[0052] Ferrous chloride: The manufacturer is Anhui Zesheng Technology Co., Ltd., with a purity of 99.5%;
[0053] Since ferric chloride and ferrous chloride are relatively expensive, they can be recovered from stainless steel pickling waste liquid. Recovery and purification are known methods and will not be described in detail here.
[0054] Eddy current thickness gauge: manufacturer is Shenyang Tianxing Testing Instrument Co., Ltd., brand ED400;
[0055] Surface roughness measuring instrument: The manufacturer is Mitutoyo Precision Measuring Instruments (Shanghai) Co., Ltd., the brand is SJ-210.
[0056] Unless otherwise specified, other materials, reagents, etc. used in the examples and comparative examples can be obtained from commercial sources.
[0057] Example 1
[0058] The present invention provides a method for annealing and pickling a stainless steel strip surface after overburning, comprising the following steps:
[0059] S1. Annealing: The uncoiled stainless steel strip is annealed; the annealing treatment includes preheating, heating, soaking, slow cooling and rapid cooling steps in sequence; wherein the preheating temperature is 550°C and the time is 25min; the heating temperature is 1000°C and the time is 1h, and the heating rate is 7.5°C / min; the soaking temperature is 1000°C and the time is 3h; the rapid cooling parameters are: reducing the temperature to 45°C and the time is 20min.
[0060] S2, pickling: add 3 times the mass of pickling solution to the annealed stainless steel strip for pickling for 8 minutes, and add corrosion inhibitor for cleaning after pickling for 2 minutes; wherein, the pickling solution includes the following components by mass percentage: 12% citric acid, 7% acetic acid, 4% tartaric acid and nano iron oxide wrapped with vitamin C, which is supplemented by water to 100%; the corrosion inhibitor includes the following components by mass percentage: 3% sodium benzoate, 1.5% nightshade extract, which is supplemented by water to 100%. The mass ratio of the pickling solution to the corrosion inhibitor is 3:1.
[0061] The method for preparing nano iron oxide coated with tartaric acid and vitamin C comprises the following steps:
[0062] Nano-iron oxide is dispersed in a mixed solution of tartaric acid and vitamin C, and a hydrothermal reaction is carried out at 160° C. for 12 hours. After cooling, the metal components are collected by a magnet, and after washing and drying, the nano-iron oxide wrapped with tartaric acid and vitamin C is obtained. The mass concentration of tartaric acid in the mixed solution of tartaric acid and vitamin C is 65%, and the concentration of vitamin C is 22%; the mass ratio of the mixed solution of tartaric acid and vitamin C to the nano-iron oxide is 5:1.
[0063] The preparation method of the nano iron oxide comprises the following steps:
[0064] Ammonium hydroxide, ferric chloride, ferrous chloride and water are mixed to obtain a mixed solution, and then a coprecipitation reaction is carried out, and the reactant is washed and dried to obtain the nano iron oxide; wherein the mass concentration of ammonium hydroxide in the mixed solution is 20-30%, the mass concentration of ferric chloride is 4-5%, and the mass concentration of ferrous chloride is 4-5%. The parameters of the coprecipitation reaction are: temperature of 20-40°C, stirring speed of 600-800rpm / min, and time of 5-7min.
[0065] Example 2
[0066] The present invention provides a method for annealing and pickling a stainless steel strip surface after overburning, comprising the following steps:
[0067] S1. Annealing: The uncoiled stainless steel strip is annealed; the annealing treatment includes preheating, heating, soaking, slow cooling and rapid cooling steps in sequence; wherein the preheating temperature is 500°C and the time is 30 min; the heating temperature is 700°C and the time is 2 h, and the heating rate is 1.7 / min; the soaking temperature is 700°C and the time is 3 h; the rapid cooling parameters are: lowering the temperature to 30°C and the time is 10 min.
[0068] S2, pickling: add 3 times the mass of pickling solution to the annealed stainless steel strip for pickling for 5 minutes, and add corrosion inhibitor for cleaning after pickling for 2 minutes; wherein, the pickling solution includes the following components by mass percentage: 10% citric acid, 5% acetic acid, 2% tartaric acid and nano iron oxide wrapped with vitamin C, which is supplemented by water to 100%; the corrosion inhibitor includes the following components by mass percentage: 2% sodium benzoate, 1% nightshade extract, which is supplemented by water to 100%. The mass ratio of the pickling solution to the corrosion inhibitor is 4:1.
[0069] The method for preparing nano iron oxide coated with tartaric acid and vitamin C comprises the following steps:
[0070] Nano-iron oxide is dispersed in a mixed solution of tartaric acid and vitamin C, and a hydrothermal reaction is carried out at 150° C. for 15 hours. After cooling, the metal components are collected by a magnet, and after washing and drying, the nano-iron oxide wrapped with tartaric acid and vitamin C is obtained. The mass concentration of tartaric acid in the mixed solution of tartaric acid and vitamin C is 60%, and the concentration of vitamin C is 20%; the mass ratio of the mixed solution of tartaric acid and vitamin C to the nano-iron oxide is 5:1.
[0071] Example 3
[0072] The present invention provides a method for annealing and pickling a stainless steel strip surface after overburning, comprising the following steps:
[0073] S1. Annealing: The uncoiled stainless steel strip is annealed at 1000°C for 3h;
[0074] S2, pickling: add 3 times the mass of pickling solution to the annealed stainless steel strip for pickling for 10 minutes, and add corrosion inhibitor for cleaning after pickling for 3 minutes; wherein, the pickling solution includes the following components by mass percentage: 15% citric acid, 10% acetic acid, 5% tartaric acid and nano iron oxide wrapped with vitamin C, which is supplemented by water to 100%; the corrosion inhibitor includes the following components by mass percentage: 5% sodium benzoate, 2% nightshade extract, which is supplemented by water to 100%. The mass ratio of the pickling solution to the corrosion inhibitor is 3:1.
[0075] The method for preparing nano iron oxide coated with tartaric acid and vitamin C comprises the following steps:
[0076] Nano-iron oxide is dispersed in a mixed solution of tartaric acid and vitamin C, and a hydrothermal reaction is carried out at 200°C for 10 hours. After cooling, the metal components are collected by a magnet, and after washing and drying, the nano-iron oxide wrapped with tartaric acid and vitamin C is obtained. The mass concentration of tartaric acid in the mixed solution of tartaric acid and vitamin C is 70%, and the concentration of vitamin C is 30%; the mass ratio of the mixed solution of tartaric acid and vitamin C to the nano-iron oxide is 6:1.
[0077] Example 4
[0078] The difference between Example 4 and Example 1 is that the mass ratio of the pickling solution to the corrosion inhibitor is 5:1.
[0079] Example 5
[0080] The difference between Example 5 and Example 1 is that the mass ratio of the pickling solution to the corrosion inhibitor is 2:1.
[0081] Comparative Example 1
[0082] The difference between Comparative Example 1 and Example 1 is that the acetic acid in the pickling solution of Comparative Example 1 is replaced by an equal amount of nitric acid.
[0083] Comparative Example 2
[0084] The difference between Comparative Example 2 and Example 1 is that in the pickling solution of Comparative Example 2, citric acid is replaced by an equal amount of nitric acid.
[0085] Comparative Example 3
[0086] The difference between Comparative Example 3 and Example 1 is that tartaric acid and vitamin C-coated nano-iron oxide are not added to the pickling solution of Comparative Example 3.
[0087] Comparative Example 4
[0088] The difference between Comparative Example 4 and Example 1 is that in the pickling solution of Comparative Example 4, the nano-iron oxide coated with tartaric acid and vitamin C is replaced with nano-iron oxide coated with hydrochloric acid and vitamin C.
[0089] Comparative Example 5
[0090] The difference between Comparative Example 5 and Example 1 is that no corrosion inhibitor is added to Comparative Example 5 after pickling.
[0091] Comparative Example 6
[0092] The difference between Comparative Example 6 and Example 1 is that the sodium benzoate in Comparative Example 6 is replaced by dimethyl phosphite.
[0093] Comparative Example 7
[0094] The difference between Comparative Example 7 and Example 1 is that no Solanum nigrum extract is added to the corrosion inhibitor of Comparative Example 7.
[0095] Comparative Example 8
[0096] The difference between Comparative Example 8 and Example 1 is that in Comparative Example 8, the pickling solution and the corrosion inhibitor are directly mixed for pickling.
[0097] Performance Testing
[0098] The annealing and pickling methods of Examples 1 to 3 and Comparative Examples 1 to 8 were used to treat three groups of 304 stainless steel with a thickness of 3.0 mm and a length and width of 4 cm respectively; wherein the 304 stainless steel was ground and polished before the test to make its surface roughness R a ≤0.25μm; After annealing, the thickness of the oxide scale on the surface of the stainless steel was tested with an eddy current thickness gauge. After pickling, the samples were washed with deionized water and dried. The oxide scale on the surface of the stainless steel was tested with an eddy current thickness gauge to test the pickling effect. The surface roughness measuring instrument was then used to test the stainless steel surface to test its corrosion performance. The lower the roughness, the lower the degree of corrosion. See Table 1 for specific data.
[0099] Table 1 Thickness and roughness of the oxide scale on the surface of stainless steel after pickling in each group
[0100]
[0101] After annealing, the surfaces of the stainless steel samples in each group had more or less blackened iron scales. After pickling, the iron scales were cleaned up by naked eyes, and the surface of the steel strip showed a metallic color. Among them, there were a few acid marks on the surface of the stainless steel strips of Comparative Examples 1 and 2. No other excessive acid defects appeared on the surfaces of the other groups.
[0102] As can be seen from Table 1, the data of the initial oxide layer are different because the annealing temperatures in Examples 2 and 3 are different from those in Example 1. However, the data can prove that the oxide scale can be effectively removed after pickling.
[0103] Comparative Examples 1 and 2 are to replace a certain organic acid in the pickling solution with nitric acid, respectively. Since the pickling time of the present invention is long, the corrosion is more serious. Generally, a strong acid is selected for pickling, and the time is controlled within 60 seconds as much as possible.
[0104] In the pickling solution of Comparative Example 3, tartaric acid and vitamin C-coated nano-iron oxide are not added, and the pickling effect is significantly reduced, indicating that tartaric acid and vitamin C-coated nano-iron oxide can increase the contact area between the pickling solution and the metal surface, which provides physical friction during the cleaning process and helps remove the oxide layer.
[0105] In the pickling solution of Comparative Example 4, the nano-iron oxide coated with tartaric acid and vitamin C is replaced with nano-iron oxide coated with hydrochloric acid and vitamin C, and its pickling performance is also reduced. Although the cleaning ability of hydrochloric acid is better than that of tartaric acid, since hydrochloric acid does not have the ability to chelate metal ions, the nano-iron oxide aggregates in the pickling solution and its dispersibility is reduced, thus affecting the pickling performance.
[0106] In Comparative Example 5, no corrosion inhibitor is added, so the surface roughness of the stainless steel increases significantly, which indicates that the pickling solution is highly corrosive to the surface. In Comparative Example 6, sodium benzoate is replaced with dimethyl phosphite, and the corrosion inhibitor of Comparative Example 7 is not added with nightshade extract, and the corrosion inhibition performance is lower than that of Example 1, indicating that the present invention selects nightshade extract and sodium benzoate for compounding, which has a synergistic effect, so that more metal surfaces are adsorbed and blocked, resulting in a significant reduction in the corrosion rate of the stainless steel surface.
[0107] Comparative Example 8 is to directly mix the pickling solution and the corrosion inhibitor for pickling. Since the pickling solution and the corrosion inhibitor have opposite effects, the direct addition of the two will reduce the pickling and corrosion inhibition performance. Therefore, the present invention first pickles and then adds the corrosion inhibitor for protection, which can effectively avoid stainless steel corrosion while ensuring the pickling effect.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for annealing and pickling a stainless steel strip after overburning, characterized in that: The following steps are involved: S1. Annealing: Annealing the stainless steel strip after uncoiling; S2, pickling: pickling the annealed stainless steel strip with a pickling solution for 5-10 minutes, adding a corrosion inhibitor for cleaning after pickling for 2-3 minutes; wherein the pickling solution comprises the following components by mass percentage: 10-15% citric acid, 5-10% acetic acid, 2-5% tartaric acid and nano iron oxide wrapped with vitamin C, which is supplemented to 100% by water; the corrosion inhibitor comprises the following components by mass percentage: 2-5% sodium benzoate, 1-2% nightshade extract, which is supplemented to 100% by water; The method for preparing nano iron oxide coated with tartaric acid and vitamin C comprises the following steps: The nano-iron oxide is dispersed in a mixed solution of tartaric acid and vitamin C, and a hydrothermal reaction is carried out at 150-200° C. for 10-15 hours. After cooling, the metal components are collected by a magnet, and after washing and drying, the nano-iron oxide coated with tartaric acid and vitamin C is obtained.
2. The annealing and pickling method for the surface of a stainless steel strip after overburning according to claim 1, characterized in that: In step S1, the annealing treatment includes preheating, heating, soaking, slow cooling and rapid cooling steps in sequence; wherein the preheating temperature is 500-600°C and the time is 20-30min; the heating temperature is 700-1000°C and the time is 1-2h; the soaking temperature is 700-1000°C and the time is 2-3h; the rapid cooling parameters are: reducing the temperature to 30-50°C and the time is 10-30min.
3. The annealing and pickling method for the surface of a stainless steel strip after overburning according to claim 2, characterized in that: If the stainless steel is austenitic stainless steel, the heating and soaking temperatures are both 900-1000°C; if the stainless steel is ferritic stainless steel, the heating and soaking temperatures are both 700-900°C.
4. The annealing and pickling method for the surface of a stainless steel strip after overburning according to claim 1, characterized in that: In step S2, the pickling parameters are: temperature of 70-75° C., steel strip speed of 15-20 m / min, and pickling time of 5-10 min.
5. The annealing and pickling method for the surface of a stainless steel strip after overburning according to claim 1, characterized in that: The mass concentration of tartaric acid in the mixed solution of tartaric acid and vitamin C is 60-70%, and the concentration of vitamin C is 1-5%; the mass ratio of the mixed solution of tartaric acid and vitamin C to nano iron oxide is (5-6):
1.
6. The annealing and pickling method for the surface of a stainless steel strip after overheating according to claim 1, characterized in that: The preparation method of the nano iron oxide comprises the following steps: Ammonium hydroxide, ferric chloride, ferrous chloride and water are mixed to obtain a mixed solution, and then a coprecipitation reaction is carried out. The reactant is washed and then dried to obtain the nano iron oxide; wherein the mass concentration of ammonium hydroxide in the mixed solution is 20-30%, the mass concentration of ferric chloride is 4-5%, and the mass concentration of ferrous chloride is 4-5%.
7. The annealing and pickling method for the surface of a stainless steel strip after overburning according to claim 6, characterized in that: The parameters of the coprecipitation reaction are: temperature of 20-40° C., stirring speed of 600-800 rpm / min, and time of 5-7 min.
8. The annealing and pickling method for the surface of a stainless steel strip after overheating according to claim 6, characterized in that: The sources of the ferric chloride and ferrous chloride are stainless steel pickling waste liquid.
9. The annealing and pickling method for the surface of a stainless steel strip after overburning according to claim 1, characterized in that: The mass ratio of the pickling solution to the corrosion inhibitor is (3~4):1.
Citation Information
Patent Citations
Nitric-acid-free stainless steel acid washing solution and preparation method thereof
CN103882455A
High-efficiency derusting solution for steel derusting
CN104087957A